2021
DOI: 10.3390/medicina57090949
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sertraline in Hemodialysis Patients

Abstract: Depression and anxiety are the most common psychiatric disorders in end-stage renal disease (ESRD) patients treated with hemodialysis (HD) and may correlate with lower quality of life and increased mortality. Depression treatment in HD patients is still a challenge both for nephrologists and psychiatrists. The possible treatment of depressive disorders can be pharmacological and non-pharmacological. In our article, we focus on the use of sertraline, the medication which seems to be relatively safe and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 145 publications
(194 reference statements)
1
9
0
Order By: Relevance
“…Also, no major adverse event, bleeding, new sexual complaint, nor QT interval prolongation were reported in the sertraline group. These findings support the data [ 17 ] suggesting that sertraline is considered a relatively safe antidepressant in dialysis patients with fewer side effects compared to other drugs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, no major adverse event, bleeding, new sexual complaint, nor QT interval prolongation were reported in the sertraline group. These findings support the data [ 17 ] suggesting that sertraline is considered a relatively safe antidepressant in dialysis patients with fewer side effects compared to other drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Sertraline hydrochloride is a SSRI which improved itching in patients with cholestatic pruritus [ 16 ]. Compared to other SSRI, sertraline is considered a safe and effective option for the treatment of depression and anxiety in ESRD patients [ 17 ]. There is paucity of data regarding effects of sertraline on UP.…”
Section: Introductionmentioning
confidence: 99%
“…Among the SSRIs, fluoxetine is the most researched, with a daily dose of 20-60 mg considered tolerable [16,68]. Another review has focused on the use of sertraline in hemodialysis and found that the use of sertraline appears to be safe but needs more investigation [69]. A double-blind randomized clinical trial found that sertraline has improved pruritis intensity in hemodialysis patients [70].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…The disease affects about 3-5% of the world's population, and more often it affects women, but the mechanism of its development has not been fully understood [1]. At the same time, the presence of a somatic disease such as Parkinson's disease, pain syndromes, malignant tumors, thyroid diseases, diabetes, heart attack, stroke, ischemic heart disease, AIDS, and Alzheimer's disease, may increase the likelihood of a depressive episode [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoxetine and sertraline belong to the SSRIs, and in addition to the treatment of depression, they also find a number of other applications, including in the treatment of anxiety disorders, eating disorders, and alcoholism [1]. Fluoxetine and sertraline may also be administered as an adjunct to cancer pain management together with essential pain relievers [1][2][3]. Fluoxetine is a frequently prescribed antidepressant and is also used in bulimia nervosa, where it reduces bulimic and depressive symptoms [10].…”
Section: Introductionmentioning
confidence: 99%